Malignant lymphoma of the cervix in a bicollis uterus considered to be a post-transplant lymphoproliferative disorder in a patient after renal transplantation: A case report - Yu Yoshida; Ririko Izumi; Saki Iwashita; Natsumi Nakashima; Kaori Kishida; Yuzo Imachi; Yukiyo Shimada; Kana Maehara; Tomoko Wada; Mariko Ando; Yoichiro Hamasaki; Shuichi Kurihara; et al. (Elsevier, 2020)
Post-transplant lymphoproliferative disorder (PTLD) refers to a group of diseases, characterized by abnormal proliferation of lymphocytes, that develop after organ transplantation. PTLD is associated with poor prognosis, and has become a major problem for transplant patients. In this report, we described a case of malignant lymphoma of the cervix in a bicollis uterus considered to be a PTLD in a patient after renal transplantation. The incidence of this disease is expected to increase as the survival rate of transplant patients improves. Hence, it is very important for gynecological oncologists to consider the presence of PTLD when examining such patients.